Contradictory effects of technological change across developed countries - Uwe Blien; Oliver Ludewig; Anja Rossen (Review of International Economics, 2022)
Will productivity gains lead to technological unemployment in a region or to new prosperity? In our article, we formally show that under general assumptions the price elasticity of demand on product markets is decisive: technological change leads to employment growth if product demand is elastic and it leads to employment decline if product demand is inelastic. In our empirical analysis, we use industry-level time series data on output, prices, employment, wages, and national income for nine countries (including Germany, UK, USA) to estimate aggregate Marshallian product demand functions based on IV regressions and state space models with time-varying coefficients. The resulting income and price elasticities are used as inputs in a second step in which we estimate the employment effects of productivity changes as interactions with the elasticities. The results correspond to theoretical expectations: demand is generally inelastic and the employment effect of technological progress is therefore moderately negative.
Keywords: 330; labor market dynamics; productivity growth; technological change